PENGARUH GAYA KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI DI DINAS SOSIAL KABUPATEN GOWA - Jannah, Miftahul; Mustari, Nuryanti; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2022)
This research intends to determine the effect of leadership style on the organizational commitment of official social of Gowa regency. The approach was taken by this research is the quantitative approach with a sample of 50 employees were taken by incidental sampling. The test instrument which is used in this research are validity and reliability test. While for analizing quantitative data used is a simple linear regression analysis. The result of the research from regression analysis reveals that leadership style have a positive effect and significantly on organizational commitment of official social of Gowa regerency. The measurement test result reveals that the most dominant variabel of official social of Gowa regerency is the leadership style (X), this is because the variable has greatest value of the cronbach’s alpha and it has smallest significance value of the other variables. The result from the research of leadership style at the District Social Service Gowa showed that the directive style was the most dominant applied. Whereas the organizational commitment found in the dominant employee is an ongoing commitment. The result of the study found there a significant effect between leadership style on organizational commitment.